Roflumilast: Review of Phosphodiesterase-4 Inhibitor as Asthma Therapy - Rafina Syfridiana; Fauna Herawati (Jurnal Ilmiah Kesehatan, 2021)
Asthma is a heterogeneous disease characterized by chronic inflammation of the airways induced reversible obstruction resulting in mortality and morbidity. Roflumilast is a second-generation selective inhibitor of phosphodiesterase-4  targeting PDE type 4 isoenzymes, disturbing the breakdown of cyclic AMP (cAMP) and reducing inflammation. However, it has not been recommended for asthma patients because of insufficient evidence from trial results. The search was carried out using the PUBMED online database from 2011 to May 2021. The keywords used in this study were "Asthma" and "Roflumilast" using the Boolean Operator "AND." All articles were published until May 7, 2021. The design of the articles involved in this study was randomized. Selection of research articles was obtained to avoid duplication of articles through title and abstract screening. Next, eligible articles were extracted by reviewing the full text according to the inclusion criteria. Finally, Five articles were used in this paper. Roflumilast can be given per-oral as a single dose or combine with ICS or montelukast. Roflumilast can increase FEV1 and reduce eosinophils, a pathological cause of asthma that induces inflammation in the airways. The side effects of roflumilast are well tolerated in asthma patients, the most common of which include headache, diarrhea, nausea, weight loss, and insomnia